0111 The association between work schedule control and nurses' burnout in taiwan. (21st August 2017) - Lin, Ting-Ti; Shiao, Judith Shu-Chu; Guo, Yue-Liang; Chen, Yi-Chuan; Li, Yu-Ju; Ho, Jiune-Jye
Abstract : Background: Shiftwork and long work hours have been reported as significant risk factors for nurses' burnout. In addition, whether nurses have ability to control their own schedule, such as having options and decision over swapping shifts or taking unpaid leave, remain lacking. Objective: To examine the associations between nurses' work schedule control (WSC) and their effect on burnout. Method: A total of 3431 fulltime registered nurses working in the hospital were systematically sampled in 2013. A structured self-administered questionnaire was performed to assess nurses' WSC, work schedule demands (WSDs) and their effect on burnout. The WSC was assessed by asking nurses' experiences of requesting leave. Personal and client burnout status were measured using the Chinese version of the Copenhagen Burnout Inventory. Multivariable logistic regression was used to analyse the associations between nurses' WSC and their effect on burnout. The WSDs, including shiftwork patterns and average weekly working hours, were controlled. Results: A total of 2631 questionnaires were eligible for final analysis. Only 5% of participants experienced unrestricted leave. After adjusting for demographic data, both average weekly working hours and unrestricted leave were significantly associated with nurses' personal and client burnout. Nurses exposed to rotating shift work were more likely to experience client burnout. Conclusion: This study identified that work schedule control (WSC) was related to personal and client burnout among hospital nurses. Hospitals wishing to proactively reduce nurses' burnout may permit more unrestricted leaves when requested by the staff nurse.